Cadmium complex crystal material and its preparation method and fluorescence identification application
By using the cadmium complex crystal materials Cd-1 and Cd-2 as fluorescence recognition sensors, the problem of difficult to detect Fe3+ and Tb3+ quickly, low cost and high sensitivity in the prior art is solved, and the rapid and sensitive detection of these metal ions is achieved, which has important application value.
Patent Information
- Application Number
- CN202510080378.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The prior art is difficult to detect Fe3+ and Tb3+ concentrations quickly, at low cost and with high sensitivity. The traditional detection methods have the disadvantages of expensive instruments, complex operation, and long-term time consuming, and it is difficult to meet the needs of intelligent control.
The cadmium complex crystal materials Cd-1 and Cd-2 are used as fluorescence recognition sensors to quickly detect Fe3+ and Tb3+ by constructing the structure with appropriate ligands. Cd-1 has a three-dimensional framework structure, and Cd-2 is a zero-dimensional structure, but a three-dimensional supramolecular structure is formed through hydrogen bonds.
It realizes fast and sensitive detection of Fe3+ and Tb3+, has low cost and portable characteristics, and is suitable for environmental protection, quality inspection and other fields, and has important application value.
Smart Images

Figure CN119504422B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of crystalline materials, and particularly relates to a cadmium complex crystal material, a preparation method thereof and a fluorescence identification application thereof. Background Art
[0002] Fe 3+ It is a vital nutrient. It is one of the indispensable elements for life activities such as hemoglobin formation, DNA synthesis and oxygen storage. The intake of appropriate amounts of iron ions can prevent certain diseases, such as heart disease, Parkinson's disease and Alzheimer's disease. However, when its concentration exceeds a certain safety threshold, it will have a negative impact on the organism and cause a series of serious physiological disorders. For example, excessive Fe 3+ It may cause insomnia symptoms, affect the body's immune function and cause it to decline. More seriously, long-term accumulation of Fe 3+ It may cause damage to the liver and even lead to serious diseases such as cirrhosis. However, with the rapid development of industry, Fe 3+ It has become an important source of inorganic pollutants. For example, in industry, a large amount of Fe 3+ The wastewater is directly discharged into rivers to pollute the environment; some iron-containing mechanical equipment or chemical additives are used in food preparation and processing, which will lead to excessive Fe 3+ When introduced into food, it will produce a series of physiological toxic effects on the human body, causing harm to people's health. 3+ The importance and impact of Fe in biological and environmental systems, therefore, the environmental Fe 3+ The detection of concentration is very important. Traditional detection methods include electrochemical method, liquid chromatography, mass spectrometry, atomic spectrophotometry, etc. However, traditional detection methods usually have disadvantages such as expensive instruments, complex and time-consuming operations, high costs, inability to provide instant data feedback, and difficulty in meeting the needs of intelligent management and control. Therefore, the development of highly sensitive and rapid specific detection methods is of great research significance.
[0003] Al 3+ It is an important element for maintaining healthy bones and nerve function, but when it is excessive, it will cause a large loss of calcium in the human body, resulting in osteoporosis; it will cause great damage to the brain nerves, causing memory and intelligence to decline; at the same time, it will inhibit the absorption of phosphorus by the human intestine, interfere with the normal calcium and phosphorus metabolism in the body, and cause a series of harms. Therefore, it is necessary to accelerate the consumption of Al 3+ Concentration detection and new Al 3+ Sensor development.
[0004] In addition, terbium (Tb) is a member of the lanthanide series. 3+It is widely used in the fields of medicine, aviation and industry. It can treat skin diseases and prepare pesticides, magnetic materials, laser materials and fluorescent materials. 3+ It has certain genetic toxicity to plant growth and poses a potential threat to organisms. 3+ Concentration testing and development of new Tb 3+ Sensors are imperative.
[0005] With the rapid development of science and technology, environmental protection and quality of life have gradually become the focus of people's attention. In this context, it is particularly important to develop a low-cost, portable, highly sensitive metal ion detection sensor that meets people's needs for precise detection. In recent years, metal ion sensors of various materials have been developed. However, new metal ion sensors that can be widely used in actual production and life are still very scarce. This is mainly because the sensitivity and accuracy of the sensor need to be further improved, so more reusable and easy-to-operate metal ion detection sensors need to be developed. Among them, fluorescence recognition technology is a commonly used metal ion recognition method with the advantages of fast analysis speed and low cost. Luminescent materials with fluorescence recognition function show broad prospects in the field of sensing.
[0006] Coordination polymers (CPs), also known as coordination compounds, are a type of compound formed by the metal center and the coordination atoms through coordination bonds. They are new organic-inorganic hybrid materials with repeating units. They have both the rigidity of inorganic materials and the flexibility of organic materials. They are different from inorganic porous materials and general organic complexes. They have the advantages of large specific surface area, designable and controllable structure and properties. The electron configuration of Cd is [Kr] 4d 10 5s 2 , Cd 2+ Common coordination numbers are 4 and 6, which make it easier to predict the structure of the complex. In addition, the complexes formed by transition metals can usually affect the luminescence of the complex through ligand-to-metal ion electron transfer (LMCT) or metal ion-to-ligand electron transfer (MLCT), and can be used as luminescent materials.
[0007] In summary, the present invention uses Cd 2+ Using appropriate ligands as the central metal ion, a type of fluorescent recognition sensor that can detect metal ions was constructed. Summary of the invention
[0008] One of the purposes of the present invention is to provide a cadmium complex crystal material. There are two types of cadmium complex crystal materials. The chemical formula of the first type is [Cd(L)(DMF)·N(CH3)2] n , named Cd-1;
[0009] The chemical formula of the second one is [Cd(H2L)2·4H2O] n , named Cd-2;
[0010] Wherein H3L is an organic ligand 4,4'-((5-carboxyl-1,3-phenylene)bis(oxy))dibenzoic acid, and the chemical structure is as follows:
[0011] .
[0012] N(CH3)2 is the dimethylamine ion, which comes from the solvent DMF.
[0013] Furthermore, from the perspective of structural connection and construction, the Cd-1 is a three-dimensional framework, and its crystal structure is a hexagonal system. P 65 space group, Cd-1 unit cell parameters are: a = 15.8932(3) Å, b = 15.8932(3) Å, c = 20.7641(8) Å, α =90.000, β = 90.000, γ = 120.000.
[0014] Furthermore, from the perspective of structural connection, Cd-2 is a zero-dimensional structure, which can form a three-dimensional supramolecular structure through H-bonding, and its crystal structure belongs to the triclinic system. P -1 space group, Cd-2 unit cell parameters are: a = 5.8374(4) Å, b = 13.6466(10) Å, c = 13.8904(9) Å, α = 109.050(2), β = 99.212(3), γ = 100.295(2).
[0015] Furthermore, the coordination number of Cd(II) in Cd-1 is 7, all of which are coordinated with O atoms, of which six O atoms come from three different ligands L 3- -COO - , one O atom comes from the coordinated DMF molecule; each Cd(II) is connected to three ligands L 3- , each ligand L 3- Connect three Cd(II);
[0016] Among them, the adjacent L 3-The ligand and Cd(II) are connected through the coordination bonds Cd1-O1, Cd1-O2, Cd1-O7, Cd1-O8 and Cd1-O9 to form a left-handed spiral chain structure. The one-dimensional spiral chain is connected to Cd(II) through the carboxyl groups where O4 and O5 are located, that is, the coordination bonds Cd1-O4 and Cd1-O5 form a three-dimensional spatial structure.
[0017] Furthermore, in Cd-2, the ligand H3L has only one -COOH deprotonated, the coordination number of Cd(II) is 6, and the six O atoms form a deformed octahedral structure with Cd(II) as the center, of which four O atoms come from the coordinated water molecules, the four oxygen atoms from the water molecules form a quadrilateral plane, and the remaining two oxygen atoms come from the ligand H2L - O atoms, therefore, Cd-2 is a zero-dimensional structure, but in space, there are strong hydrogen bonds between multiple zero-dimensional structures, forming a three-dimensional structure through hydrogen bonds O1—H1···O8, O6—H6A···O7, O9—H9A.
[0018] The present invention also provides a method for preparing the cadmium complex crystal material Cd-1, comprising the following steps:
[0019] Weigh CdSO4·8 / 3H2O and ligand H3L into a 20.0 ml pressure-resistant thick glass sample bottle, and measure the mixed solution of DMF / ethanol / water into the above glass sample bottle. Finally, cover the bottle cap and seal the sample bottle, place it in a forced air drying oven, and heat it at 90.0℃ for 3 days. After the system slowly cools to room temperature, take out the sample bottle to obtain a colorless block complex Cd-1.
[0020] Furthermore, the added mass of the CdSO4·8 / 3H2O is (20.5-30.7) mg, and the added mass of the ligand H3L is (15.8-25.6) mg.
[0021] Furthermore, the volume ratio of DMF, ethanol and water in the mixed solution is (2-5):2:1.
[0022] The present invention also provides a method for preparing the cadmium complex crystal material Cd-2, comprising the following steps:
[0023] Weigh CdSO4·8 / 3H2O and ligand into a 20.0 ml pressure-resistant thick glass sample bottle, and measure the mixed solution of DMF and water into the above glass sample bottle. Finally, cover the bottle cap and seal the sample bottle, place it in a forced air drying oven, and heat it at 90.0℃ for 3 days. After the system slowly cools to room temperature, take out the sample bottle to obtain a colorless block complex Cd-2.
[0024] Furthermore, the added mass of the CdSO4·8 / 3H2O is (20.5-30.7) mg, the added mass of the ligand H3L is (15.8-25.6) mg, and the volume ratio of DMF and water in the mixed solution is (1-3):2.
[0025] The present invention also provides application of the cadmium complex crystal materials Cd-1 and Cd-2 in metal ion recognition.
[0026] Furthermore, the metal ion is Fe 3+ and Tb 3+ .
[0027] Compared with the prior art, the present invention has the following technical effects: the present invention selects Cd 2+ As the central metal ion, the flexible polycarboxylic acid ligand 4,4'-((5-carboxyl-1,3-phenylene)bis(oxy))dibenzoic acid was selected to synthesize two novel cadmium complexes Cd-1 and Cd-2. The Cd-1 and Cd-2 prepared by the present invention can quickly detect Fe 3+ and Tb 3+ , can be used as a new type of fluorescence recognition sensor. This material can be used in environmental protection, quality inspection and other fields, and is of great significance for protecting the environment and improving food quality and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the coordination environment of Cd(II) in Cd-1 (symmetry code: ⅰ 1-y, 1+xy, -0.33333+z. ⅱ 1+xy, x, -0.16667+z. ⅲ -x+y, 1-x, 0.33333+z. ⅳ y,1-x+y, 0.16667+z.).
[0029] Figure 2 This is the one-dimensional spiral chain structure diagram of Cd-1.
[0030] Figure 3 This is the stacking diagram of the one-dimensional spiral chain in Cd-1.
[0031] Figure 4 The one-dimensional spiral chain in Cd-1 is connected by the coordination bonds Cd1-O4 and Cd1-O5 to form a three-dimensional structure. Purple solid line: Cd1-O4; blue solid line: Cd1-O5.
[0032] Figure 5 Schematic diagram of the coordination environment of Cd(II) in Cd-2 (symmetry code: i-x, 2-y, 2-z.).
[0033] Figure 6This is a three-dimensional framework diagram formed by hydrogen bonding in Cd-2. Green dotted line: O1—H1···O8; orange dotted line: O10—H10A···O2; purple dotted line: O9—H9A···O5; black dotted line: O6—H6A···O7; green dotted line: O9—H9B···O7.
[0034] Figure 7 Thermogravimetric analysis diagrams of Cd-1 and Cd-2.
[0035] Figure 8 This is the infrared spectrum of the Cd-1 sample of the present invention.
[0036] Fig. 9 This is the infrared spectrum of the Cd-2 sample of the present invention.
[0037] Fig.10 It is the solid-state fluorescence emission spectrum of Cd-1 and Cd-2 and their ligand H3L of the present invention.
[0038] Fig.11 The present invention Cd-1 in 10 -3 Fluorescence emission spectra in mmol / mL NaNO3, Al(NO3)3, KNO3, Fe(NO3)3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, and Pb(NO3)2 solutions.
[0039] Fig.12 The present invention Cd-1 in 10 -3 Bar graph of emission peak intensity near 340 nm in mmol / mL NaNO3, Al(NO3)3, KNO3, Fe(NO3)3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, and Pb(NO3)2 solutions.
[0040] Fig.13 Cd-1 blank and Fe 3+ The image was taken under ultraviolet light at a wavelength of 365nm.
[0041] Fig.14 Cd-1 blank and Al added 3+ The image was taken under ultraviolet light at a wavelength of 365nm.
[0042] Fig.15 The present invention Cd-1 in 10 -3Fluorescence emission spectra in mmol / mL rare earth salts Y(NO3)3, La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3 solutions.
[0043] Fig.16 The present invention Cd-1 in 10 -3 Bar chart of the strongest emission peak intensity near 340nm in mmol / mL rare earth salt solutions of Y(NO3)3, La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3.
[0044] Fig.17 Cd-1 blank and Tb added 3+ The image was taken under ultraviolet light at a wavelength of 365nm.
[0045] Fig.18 The present invention Cd-2 in 10 -3 Fluorescence emission spectra in mmol / mL NaNO3, Al(NO3)3, KNO3, Fe(NO3)3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, and Pb(NO3)2 solutions.
[0046] Fig.19 The present invention Cd-2 in 10 -3 Bar graph of the strongest emission peak intensity near 350 nm in mmol / mL NaNO3, Al(NO3)3, KNO3, Fe(NO3)3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, and Pb(NO3)2 solutions.
[0047] Fig. 20 Cd-2 blank and Fe 3+ The image was taken under ultraviolet light at a wavelength of 365nm.
[0048] Fig.21 Cd-2 blank and Al added 3+ The image was taken under ultraviolet light at a wavelength of 365nm.
[0049] Fig. 22The present invention Cd-2 in 10 -3 Fluorescence emission spectra in mmol / mL rare earth salts Y(NO3)3, La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3 solutions.
[0050] Fig.23 The present invention Cd-2 in 10 -3 Bar chart of emission peak intensity near 350 nm in mmol / mL rare earth salt solutions of Y(NO3)3, La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3.
[0051] Fig.24 Cd-2 blank and Tb added 3+ The image was taken under ultraviolet light at a wavelength of 365nm. DETAILED DESCRIPTION
[0052] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0053] Example 1
[0054] CdSO4·8 / 3H2O (20.5 mg) and ligand H3L (20.0 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / ethanol / water (volume ratio 5:2:1) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-1.
[0055] Example 2
[0056] CdSO4·8 / 3H2O (25.6 mg) and ligand H3L (20.0 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / ethanol / water (volume ratio 5:2:1) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-1.
[0057] Example 3
[0058] CdSO4·8 / 3H2O (30.7 mg) and ligand H3L (20.0 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / ethanol / water (volume ratio 5:2:1) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-1.
[0059] Example 4
[0060] CdSO4·8 / 3H2O (25.6 mg) and ligand H3L (15.8 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / ethanol / water (volume ratio 5:2:1) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-1.
[0061] Example 5
[0062] CdSO4·8 / 3H2O (25.6 mg) and ligand H3L (25.6 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / ethanol / water (volume ratio 5:2:1) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-1.
[0063] Example 6
[0064] CdSO4·8 / 3H2O (25.6 mg) and ligand H3L (20.0 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / ethanol / water (volume ratio 2:2:1) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-1.
[0065] The crystal structures obtained in Examples 1-6 are the same.
[0066] Example 7
[0067] CdSO4·8 / 3H2O (20.5 mg) and ligand H3L (20.0 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / water (volume ratio 1:2) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-2.
[0068] Example 8
[0069] CdSO4·8 / 3H2O (25.6 mg) and ligand H3L (20.0 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / water (volume ratio 1:2) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-2.
[0070] Example 9
[0071] CdSO4·8 / 3H2O (30.7 mg) and ligand H3L (20.0 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / water (volume ratio 1:2) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-2.
[0072] Example 10
[0073] CdSO4·8 / 3H2O (25.6 mg) and ligand H3L (15.8 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / water (volume ratio 1:2) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-2.
[0074] Embodiment 11
[0075] CdSO4·8 / 3H2O (25.6 mg) and ligand H3L (25.6 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / water (volume ratio 1:2) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-2.
[0076] Example 12
[0077] CdSO4·8 / 3H2O (25.6 mg) and ligand H3L (20.0 mg) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 8.0 ml of DMF / water (volume ratio 3:2) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain Cd-2.
[0078] The crystal structures obtained in Examples 7-12 are the same.
[0079] See below for details:
[0080] (1) Crystal structure determination:
[0081] Crystals with better growth and fewer cracks were selected and glued to a thin glass wire. The diffraction data of Cd-1 and Cd-2 were collected under Mo-Kα radiation (λ = 0.71073 Å) at room temperature using a BrukerAPEX-II CCD single crystal diffractometer. Cd-2 was refined using Shellxl-2018 in the OLEX2 program. The structure was solved using the XS structure solver, and the SHELXTL software package was used for least squares optimization. In the process of improvement, the anisotropic displacement parameters of non-hydrogen atoms were given. The positions of hydrogen atoms on the ligands were determined using the theoretical hydrogenation method. The crystallographic data are shown in Table 1.
[0082] Table 1 Crystallographic data of Cd-1 and Cd-2 materials
[0083]
[0084] The structure of the complex Cd-1 is shown in Figure 1 , Figure 2 , Figure 3 and Figure 4 As shown, Figure 1 is the coordination environment of Cd(II), indicating that the coordination number of Cd(II) in Cd-1 is 7, all of which are coordinated with O atoms, of which six O atoms come from three different ligands L 3- -COO - , one O atom comes from the coordinated DMF molecule; each Cd(II) is connected to three ligands L 3- , each ligand L 3- Connect three Cd(II); Figure 2 The one-dimensional spiral chain structure of Cd-1 is shown in Figure 1. Figure 3 The stacking diagram of the one-dimensional spiral chain in Cd-1 shows that: adjacent L 3- The ligand and Cd(II) are connected through the coordination bonds Cd1-O1, Cd1-O2, Cd1-O7, Cd1-O8 and Cd1-O9 to form a left-handed spiral chain structure. Figure 4 For L 3- The three-dimensional structure composed of Cd(II) shows that the one-dimensional spiral chain in Cd-1 is connected by the coordination bonds Cd1-O4 and Cd1-O5 to form a three-dimensional structure diagram.
[0085] The structure of the complex Cd-2 is shown in Figure 5 and Figure 6 As shown, Figure 5 Schematic diagram of the coordination environment of Cd(II) in Cd-2. In Cd-2, the ligand H3L has only one -COOH deprotonated, and the coordination number of Cd(II) is 6. Six O atoms form a deformed octahedral structure with Cd(II) as the center, of which four O atoms come from coordinated water molecules, and the four oxygen atoms from water molecules form a quadrilateral plane. The remaining two oxygen atoms come from the ligand H2L. - O atoms, therefore, Cd-2 is a zero-dimensional structure, but in space, there are strong hydrogen bonds between multiple zero-dimensional structures, and three-dimensional structures are formed through hydrogen bonds O1—H1···O8, O6—H6A···O7, O9—H9A, see Figure 6 .
[0086] Generally speaking, complexes with good thermal stability are more suitable for identification materials and are easier to apply to high temperature and complex environments. The thermal degradation process of complexes is often accompanied by the breaking of coordination bonds and the combustion of ligands. Therefore, the thermal stability of complexes is generally related to the strength of coordination bonds and the number of links of node ligands. 2+ The coordination numbers of Cd-1 and Cd-2 are 4, 5 and 6. 2+ The coordination numbers of Cd-1 and Cd-2 are 7 and 6 respectively, and Cd-1 carries one coordinated DMF molecule. The crystal material of the present invention is novel, and each Cd(II) in Cd-1 is connected to three L 3- Ligand, each L 3- The ligand connects three Cd(II), L 3- The ligand and Cd(II) are interconnected to form a three-dimensional structure; although the Cd-2 complex structure is a 0D structure, there are intermolecular forces such as hydrogen bonds between adjacent structures, which increases the stability of the complex structure. Figure 7 ), Cd-1 loses about 11.2% of its weight before 235℃, which is consistent with the weight loss of the coordinating solvent molecule DMF (actually about 11.7%). A second weight loss platform appears around 375℃, and the weight loss is about 6.9% between 375℃ and 417℃. This weight loss platform is the weight loss of free dimethylammonium ions (actually about 7.1%). There is no obvious weight loss platform after that, and the structure of Cd-1 gradually collapses. Cd-2 is at 105 o The first weight loss occurs near C, weighing about 10.0%, which is mainly caused by the free solvent molecules on the surface of the complex. o C-330 o The second weightlessness platform is between C and C, which corresponds to four coordinated water molecules (actually about 7.4%). After that, the weightlessness is obvious, indicating that the structure collapses, which shows that Cd-2 can be stable to 330 oC, which is basically consistent with the molecular formula in single crystal analysis. Good thermal stability is conducive to the application and promotion of Cd-1 and Cd-2.
[0087] The infrared spectra of Cd-1 and Cd-2 were detected by Shimadzu FTIR-8400S spectrometer at 4000-500 cm −1 The FT-IR spectra of Cd-1 and Cd-2 were collected within the range of , and the corresponding characteristic absorption peaks were characterized. The material composition was analyzed by the distribution of characteristic peaks in the infrared spectrum. Figure 8 and Fig. 9 By measuring the distribution of the absorption characteristic peaks of Cd-1 and Cd-2 in the infrared spectrum, it is shown that -COO - Participated in coordination. The main absorption peaks of Cd-1 are as follows: 1393 (s), 1557 (m), 1597 (m), 1655 (m), 1220 (m), 1164 (w), 1121 (m), 1164 (w), 1112 (w), 1000 (w), 864 (w), 784 (w). The main absorption peaks of Cd-2 are as follows: 3403 (m), 1703 (w), 1660 (m), 1598 (s), 1550 (s), 1393 (s), 1281 (m), 1221 (s), 1164 (w), 1120 (w), 1002 (w), 782 (m), which confirms the coordination between metal and ligand.
[0088] Solid-state fluorescence emission spectra of the ligand, Cd-1 and Cd-2 were tested. The results are shown in Fig.10 When the excitation wavelength is 250nm, within the scanning range of 300-550nm, the solid-state fluorescence emission spectrum shows that the strongest emission peak of the ligand H2L is at 362nm, with shoulder peaks at 400nm and 455nm; Cd-1 has the strongest emission peak at 346nm, with shoulder peaks at 443nm and 462nm; Cd-2 has the strongest emission peak at 336nm, with shoulder peaks at 439nm and 457nm. The emission spectra of the complexes Cd-1 and Cd-2 are similar to those of the ligands, indicating that the luminescence of the complexes mainly comes from the luminescence of the ligands. Compared with the ligands, the main peaks and shoulder peaks of the complexes have a slight blue shift or red shift, which is mainly caused by the coordination electron transition between the ligands and the metal ions.
[0089] Fig.11 Figure 2 is the fluorescence emission spectra of Cd-1 in different non-rare earth metal ion solutions. -3mmol / mL NaNO3, Al(NO3)3, KNO3, Fe(NO3)3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, and Pb(NO3)2 solutions, the results showed that the emission spectra had similar shapes, with the strongest emission peak near 340 nm, but different fluorescence intensities. 3+ The fluorescence quenching is caused in the solution, so the Cd-1 to Fe 3+ It has fluorescent recognition function. Fig.12 The strongest emission peak intensity bar chart of Cd-1 in different non-rare earth metal ion solutions. The strongest emission peak fluorescence intensity is different. + Highest medium strength, Fe 3+ Medium intensity is the lowest.
[0090] Fig.13 Cd-1 blank and Fe 3+ The image was taken under ultraviolet light at a wavelength of 365nm. Fig.14 Cd-1 blank and Al added 3+ The picture is taken under 365nm ultraviolet light. It can be seen that the addition of Al 3+ After the addition of Fe³⁺ ions, the fluorescence intensity decreased, but after the addition of Fe³⁺ ions, the fluorescence disappeared completely.
[0091] Fig.15 Figure 2 is the fluorescence emission spectra of Cd-1 in different rare earth metal ion solutions. -3 In mmol / mL rare earth salt solutions of Y(NO3)3, La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3, the fluorescence emission spectra have similar shapes, with the strongest emission peak near 340 nm, but different fluorescence intensities. Compared with the blank sample, the peaks of all rare earth ions were weakened. In addition, Cd-1 3+ In addition to the emission peak near 350 nm, there are stronger emission peaks at 488 nm, 543 nm, 583 nm, and 620 nm. These peaks are Tb 3+ The characteristic peak of Cd-1 to Tb 3+ It also has a certain identification function. Fig.16 The strongest emission peak intensity bar graph of Cd-1 in different rare earth metal ion solutions. 3+ The highest strength is Eu 3+ Medium intensity is the lowest. Fig.17 Cd-1 blank and Tb added 3+ The image was taken under 365nm ultraviolet light. 3+ After that, the color of the fluorescence changes from blue to yellow.
[0092] Fig.18 Figure 2 is the fluorescence emission spectra of Cd-2 in different non-rare earth metal ion solutions. -3 mmol / mL NaNO3, Al(NO3)3, KNO3, Fe(NO3)3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, and Pb(NO3)2 solutions have similar emission spectra with the strongest emission peak at around 350 nm, but different fluorescence intensities. 3+ In solution, it leads to fluorescence quenching, so Cd-2 has no effect on Fe 3 + It has fluorescent recognition function.
[0093] Fig.19 The bar graph shows the strongest peak emission intensity of Cd-2 in different non-rare earth metal ion solutions. -3 mmol / mL NaNO3, Al(NO3)3, KNO3, Fe(NO3)3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, Pb(NO3)2 solutions, the strongest emission peak fluorescence intensity is different. When Fe 3+ The fluorescence is quenched in solution.
[0094] Fig. 20 Cd-2 blank and Fe 3+ The image was taken under ultraviolet light at a wavelength of 365nm. Fig.21 Cd-2 blank and Al added 3+ The picture is taken under 365nm ultraviolet light. It can be seen that the addition of Al 3+ After the addition of Fe³⁺ ions, the fluorescence intensity decreased, but after the addition of Fe³⁺ ions, the fluorescence disappeared completely.
[0095] Fig. 22 Figure 2 is the fluorescence emission spectra of Cd-2 in different rare earth metal ion solutions. -3In mmol / mL rare earth salt solutions of Y(NO3)3, La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3, the shapes of the fluorescence emission spectra are similar, but the fluorescence intensities are different. 3+ In addition to the emission peak near 350 nm, there are strong emission peaks at 488 nm, 543 nm, 583 nm, and 620 nm. These peaks are Tb 3+ The characteristic peak of this complex is 3+ It has a certain recognition function. Cd-2 in Tb 3+ In addition to the emission peak near 350 nm, there are stronger emission peaks at 488 nm, 543 nm, 583 nm, and 620 nm. These peaks are Tb 3+ The characteristic peak of Cd-2 to Tb 3+ It also has a certain identification function.
[0096] Fig.23 The bar graph shows the emission peak intensity of Cd-2 at 350 nm in different rare earth metal ion solutions. -3 In mmol / mL rare earth salt solutions of Y(NO3)3, La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3, the emission peak intensities were different, but the fluorescence intensity was both enhanced and weakened compared with the blank sample. In La 3+ The highest strength is Eu 3+ Lowest intensity.
[0097] Fig.24 Cd-2 blank and Tb added 3+ The image was taken under 365nm ultraviolet light. 3+ After that, the color of the fluorescence changes from blue to yellow.
[0098] In summary, Cd-1 and Cd-2 were added to a 0.001 mmol / mL metal salt solution prepared with ethanol as the solvent, and the sample without metal salt was used as a blank control. For Cd-1, compared with the blank control, the position of the strongest emission peak did not change much, both around 340 nm, but the fluorescence intensity of the strongest emission peak changed significantly. After the addition of non-rare earth metal ions, the order of fluorescence intensity change was: Ag + >Na + >Blank>Cd 2+ >K + >Ni 2+ >Zn 2+ >Co 2+ >Cu 2+ >Pb 2+ >Al 3+ >Fe 3+ After the addition of rare earth ions, the main emission peak is between 336 nm and 348 nm, and the order of change of the fluorescence intensity of the main emission peak is: blank>Gd 3+ >Pr 3+ >La 3+ >Sm 3+ >Lu 3+ >Tb 3+ >Nd 3+ >Dy 3+ >Tm 3+ >Y 3+ >Yb 3+ > 3+ >Er 3+ >Eu 3+ It can be seen that the addition of Ag + and Na + The fluorescence intensity of the strongest emission peak is slightly enhanced. + and Na + In addition, the addition of other metal ions weakened the fluorescence of the strongest emission peak near 340 nm, especially when Fe 3+ 、Al 3+ , Pb 2+ and Eu 3+ When the fluorescence intensity was significantly weakened, the intensity quenching rates were 99.9%, 88.2%, 74.3% and 61.1% respectively. 3+ 、Al 3+ , Pb 2+ and Eu 3+ All have certain recognition functions. 3+ , Pb 2+ and Eu 3+ Compared with Fe, Cd-1 3+ The recognition effect of Cd-1 is better. 3+In addition to the emission peak near 350 nm, there are stronger emission peaks at 488 nm, 543 nm, 583 nm, and 620 nm. These peaks are Tb 3+ The characteristic peak of Cd-1 to Tb 3+ It also has a certain identification function.
[0099] For Cd-2, compared with the blank control, the position of the strongest emission peak did not change much, between 345 nm and 352 nm, but the fluorescence intensity of the strongest emission peak changed significantly. After the addition of non-rare earth metal ions, the order of change of the fluorescence intensity of the strongest emission peak was: Pb 2+ >K + >Blank>Na + >Zn 2+ >Ag + >Cd 2+ >Cu 2+ >Co 2+ >Ni 2+ >Al 3+ >Fe 3+ After the addition of rare earth ions, the strongest emission peak is between 345 nm and 352 nm, and the order of fluorescence intensity change is: La 3+ >Pr 3+ >Nd 3+ >Blank>Lu 3+ >Gd 3+ >Sm 3+ >Tm 3+ > 3+ >Yb 3+ >Tb 3+ >Y 3+ >Dy 3+ >Er 3+ >Eu 3+ It can be seen that for non-rare earth metal ions, adding Pb 2+ and K + The intensity of the strongest peak after the addition of Fe 3+ and Al 3+ When the fluorescence intensity was significantly weakened, the intensity quenching rates were 99.6% and 93.7%, respectively. 3+ and Al 3+ All have certain recognition functions. 3+ Compared with Fe, Cd-2 3+ The recognition effect of Cd-2 is better. 3+In addition to the emission peak near 350 nm, there are stronger emission peaks at 488 nm, 543 nm, 583 nm, and 620 nm. These peaks are Tb 3+ The characteristic peak of Cd-2 to Tb 3+ It also has a certain identification function.
Claims
1. A cadmium complex crystal material, characterized in that: The chemical formula is C 26 H 26 N2O9Cd, named Cd-1; The preparation method of Cd-1 comprises the following steps: weighing CdSO4·8 / 3H2O and ligand H3L and dissolving them in a mixed solution of DMF / ethanol / water; sealing, heating at a constant temperature of 90.0°C for 3 days, and obtaining a colorless block complex Cd-1 after cooling to room temperature; The added mass of the CdSO4·8 / 3H2O is 20.5-30.7 mg, and the added mass of the ligand H3L is 15.8-25.6 mg; the volume ratio of DMF, ethanol and water in the mixed solution is 2-5:2:1; From the perspective of structural connection and construction, the Cd-1 is a three-dimensional framework, and its crystal structure is a hexagonal system. P 65 space group, Cd-1 unit cell parameters are: a = 15.8932(3) Å, b = 15.8932(3) Å, c = 20.7641(8) Å, α = 90.000, β =90.000, γ = 120.000; H3L is 4,4'-((5-carboxy-1,3-phenylene)bis(oxy))dibenzoic acid, and its chemical structure is as follows: 。 2. A cadmium complex crystal material, characterized in that: The chemical formula is C 42 H 34 O 20 Cd, named Cd-2; Cd-2 is a zero-dimensional structure, which can form a three-dimensional supramolecular structure through H-bonding. Its crystal structure belongs to the triclinic system. P -1 space group, Cd-2 unit cell parameters are: a = 5.8374(4) Å, b = 13.6466(10) Å, c = 13.8904(9) Å, α = 109.050(2), β = 99.212(3), γ = 100.295(2); The preparation method of Cd-2 comprises the following steps: Weigh CdSO4·8 / 3H2O and ligand H3L and dissolve them in a mixed solution of DMF and water; seal the container, heat it at 90.0°C for 3 days, and then cool it to room temperature to obtain a colorless block complex Cd-2; The added amount of the CdSO4·8 / 3H2O is 20.5-30.7 mg, the added amount of the ligand H3L is 15.8-25.6 mg, and the volume ratio of DMF to water in the mixed solution is 1-3:
2.
3. A cadmium complex crystal material as claimed in any one of claims 1 to 2 in Fe 3+ 、A1 3+ , Tb 3+ Applications in ion recognition.
Citation Information
Patent Citations
Application of cadmium complex in Fe < 3 + > fluorescence detection
CN118324784A
3,5-di (4-carboxy phenoxy) benzene carbonic acid-and its preparing method
CN1850767A